Development of the narrative in hospitalized students of Lima - Ledesma Pérez, Fernando (2019)
Hospital pedagogy is an educational modality considered by some within the scope of inclusive education and by others as a service within special education, as it preferentially serves chronic hospitalized, terminal and, to a lesser extent, transient hospitalized patients. and with reversible pathologies. The objective of the research was to understand the experiences of company / loneliness, protection / helplessness and security / fear in hospitalized students through their narrative; the general theory was the symbolic interactionism, the substantive theory was the hospital pedagogy and the thematic unit the narrative; was carried out through the qualitative approach, ethnomethodological methods and observation, with a sample of eight hospitalized students with whom the semi-structured interview was used, guided by an interview script, the results were subjected to content analysis, it was concluded that through the narrative hospitalized children showed predominance of feelings of companionship compared to those of loneliness, predominance of feelings of protection against those of helplessness and predominance of feeling of security against those of fear, they needed to be heard, understood and also receive a specialized education . It is recommended that future research address the phenomenon of research in populations of different regions and with a diachronic design.